GENE FLOW BETWEEN MAIZE COMMERCIALIZED BY DICONSA AND NATIVE POPULATIONSAT THE MIXTECA OF PUEBLA - Carreón-Herrera Nayeli Itzell; López-Sánchez Higinio; Gil-Muñoz Abel; Antonio López Pedro; Gutiérrez- Espinosa M. Alejandra; Valadez-Moctezuma, Ernestina (Revista Mexicana de Ciencias Agrícolas, 2018)
Several papers have noted that, a possible source of transgenes detected in native maize in Mexico, could have been the grains from Diconsa’s rural stores; which produced plants that released pollen into the environment. Up to this date, there are no papers which would help to decide on the validity of such assertion. This research was conducted aiming to determining whether if the plants from grains expended by Diconsa’s rural stores can be adapted to the Mixteca’s conditions, if they achieve anthesis and if this stage coincides with the female’s flowering of the native maize of that region. 23 maize samples from Diconsa’s rural stores, 46 native populations and three commercial controls were evaluated during 2008, in two locations through a lattice design 8∗9 with two replicates. The morphological, agronomic variables and f lowering dynamics were recorded. The data analysis with univariate and multivariate techniques revealed that, the maize populations derived from maize grain from Diconsa’s rural stores was a set morphologically and agronomically different to that formed by the native populations; their plants reached anthesis and its flowering periods overlapped with those of the native populations. This shows that, in the Mixteca of Puebla, gene flow between introduced materials and native maize populations is quite possible, representing an effective way to spread transgenes if these are in the pollen grains.